PENGARUH INTEREST BASED INCOME, FEE BASED INCOME DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP RETURN ON ASSETS (ROA) - fachri Husein Al Farizi; Bani Saad (Ibs Press, 2024)
This study aims to determine Interest Income, Fee Based Income, Capital Adequacy Ratio and Return On Asset in conventional bank BUMN in Indonesia. This study uses data from 4 BUMN conventional banking that have been listed on the Indonesia Stock Exchange. Hyphotesys in this study was tested by descriptive statistics and using multiple regression analysis. The result of this study show that interest income has a negative effect, fee-based income has no effect, and capital Adequacy ratio has a positive effect on return on assets for the 2017Q1 – 2021Q4 period.